Unraveling the mysteries of the gut-kidney axis: the protective role of traditional Chinese medicine in chronic kidney disease - Li, Jiahui; Diao, Lijia; Li, Menglin; Huang, Fugang; Sun, Ke (Frontiers in Microbiology, 2025)
Chronic kidney disease (CKD) constitutes a globally progressive nephropathy orchestrating inexorable deterioration of renal architecture. The paradigmatic gut-kidney axis unveils sophisticated bidirectional interplay between enteric microbiome and renal homeostatic equilibrium. Dysbiotic perturbations catalyze aberrant accumulation of gut-derived uremic metabolites, attenuate intestinal epithelial fortification, and propagate subclinical inflammatory cascades, synergistically precipitating CKD trajectory acceleration. Contemporary therapeutic arsenals targeting this axis encompass probiotic reconstitution, prebiotic orchestration, synbiotic hybridization, precision nutritional calibration, and enteral sequestrants including AST-120. Traditional Chinese Medicine (TCM) paradigms deploy multifaceted strategies through meticulous microbiota choreography, mucosal barrier reinforcement, and renal fibrogenesis attenuation. Distinguished phytotherapeutics including Rhubarb (Rhei Radix et Rhizoma), Salvia miltiorrhiza, and Poria cocos, synergized with bioactive constituents curcumin and punicalagin, orchestrate nephroprotective virtuosity via intricate microbiome-metabolome networks. Sophisticated polyherbal architectures, exemplified by YQHG and YSHS, harmoniously fortify intestinal impermeability while nullifying uremic translocation. These revelations substantiate the transformative potential of integrative paradigms amalgamating TCM-based phytomedicine with microbiota-directed precision therapeutics for CKD stewardship.